Sub case origin fatigue in teeth of helical gear of a TA 67n turbo reducer. (January 2020) - Ruchert, C.O.F.T.; Maciel, C.I.S.; Chemin, A.E.A.
Highlights: It investigated the failures classified as subcase origin fatigue and further case crushing. The microstructural analysis of failure surface shown the retained austenite between the lath martensite. Cracks nucleated preferentially in the sublayer. Abstract: The main aim of this study is investigating the possible failures classified as subcase origin fatigue and further case crushing. Because of these failure mechanisms, the teeth of the intermediate gears shaft may fracture after several cycles of operation of the whole gearbox. Shafts are used to machines which need to transmit rotary motion into a system of parts, such as roller bearings, gears, and pulleys. In this work, a helical gear manufactured with DIN 18CrNiMo7-6 steel is an integral part of a turbo reducer, had several teeth fractured after three months of operation. The teeth were heat treated as follow: carburizing, quenching, tempering following by grinding with grinding wheels resulting in a surface hardness of the teeth between 58 and 62 HRC. The analysis of failure surface shown a bright area between the lath martensite, which is retined austenite, that decreases the contact fatigue strength. The plastic deformation transforms the retained austenite to untempered martensite, promoting the weakening of the hardened layer. The performance of composition analysis, macromolecular, optical microscopy, microhardness, and scanning electron microscopy, makes possible identifying that the crack nucleates close to the pitting corrosion line between the flank and the working face of the gear tooth. Cracks nucleated preferentially in the sublayer and propagated because of the contact fatigue, usually, pull out the upper part of the tooth entirely, which results in static propagation by the case crushing mechanism.